Medical Card coverage and the impact of income limit freezes - Claire Keane; Simona Sándorová; Brendan Walsh (The Economic and Social Research Institute (ESRI), 2025)
Ireland is one of the few European countries without a universal healthcare system (UHC). Instead, a complex system of means-tested schemes that provide free access to various healthcare services or reduced cost medication exist. The most central component of this complex system is the Medical Card scheme, which is used to cover primary, community, and acute hospital healthcare costs for lower income groups. Despite the importance of the scheme, income limits for the scheme for most population groups have not increased since 2005, despite price inflation of 26% and wage inflation of 45% since then. To prevent the loss of Medical Cards due to social welfare benefit increases, a rule was introduced allowing those solely on welfare to retain their cards even if they were above the income limit. This decision created horizontal inequity and a work disincentive, whereby families who have the same income amount are treated differently if some of their income comes from employment. This research examines Medical Card coverage across different societal groups and estimates the impact of this lack of indexation on card holding. We estimate that cardholder numbers would be significantly higher if income limits had kept pace with inflation and that over 80,000 (or 6% of cardholders) now qualify due to the social welfare rule. The study highlights the horizontal inequity and work disincentive created by the social welfare rule and the need for indexation of income limits to ensure access to necessary medical care for those in lower income deciles.
Keywords: I13; I14; I38; 330; health policy; means-tested programme; indexation; benefit erosion